Differential incremental value of ultrasound carotid intima–media thickness, carotid plaque, and cardiac calcium to predict angiographic coronary artery disease across Framingham risk score strata in the APRES multicentre study. (10th September 2015) - Gaibazzi, Nicola; Rigo, Fausto; Facchetti, Rita; Carerj, Scipione; Giannattasio, Cristina; Moreo, Antonella; Mureddu, Gian Francesco; Salvetti, Massimo; Grolla, Elisabetta; Faden, Giacomo; Cesana, Francesca; Faggiano, Pompilio
Abstract: Aims: According to recent data, more accurate selection of patients undergoing coronary angiography for suspected coronary artery disease (CAD) is needed. From the Active PREvention Study multicentre prospective study, we further analyse whether carotid intima–media thickness (cIMT), carotid plaques (cPL), and echocardiographic cardiac calcium score (eCS) have incremental discriminatory and reclassification predictive value for CAD over clinical risk score in subjects undergoing coronary angiography, specifically depending on their low, intermediate, or high class of clinical risk. Methods and results: In eight centres, 445 subjects without history of prior CAD but with chest pain of recent onset and/or a positive/inconclusive stress test for ischaemia prospectively underwent clinically indicated elective coronary angiography after cardiac and carotid ultrasound assessments with measurements of cIMT, cPL, and eCS. The study population was divided into subjects at low (10%), intermediate (10–20%), and high (>20%) Framingham risk score (FRS). Ultrasound parameters were tested for their incremental value to predict CAD over FRS, in each pre-test risk category. No significant difference could be appreciated between the discrimination value of FRS and Diagnostic Imaging for Coronary Artery Disease score for the presence of CAD. eCS or cPL demonstrated significant incremental prediction over FRS, consistently in the three FRS categories ( P < 0.01); this applied to both discrimination and reclassification, with the exception of high-risk subjects, in whom cPL was apparently not incremental over FRS, and eCS was only of borderline significance for better discrimination. Conclusions: Ultrasound eCS and cPL assessments were significant predictors of angiographic CAD in patients without prior CAD but with signs or symptoms suspect for CAD, independently and incrementally to FRS, across all pre-test risk probability strata, although in high-risk subjects, only eCS maintained an incremental value. The use of cIMT was not significantly incrementally useful in any FRS risk category.